2022
DOI: 10.3389/fpubh.2022.899582
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Impacts of Temporomandibular Disorders Symptoms and Tooth Loss on Psychological States and Oral Health-Related Quality of Life During the COVID-19 Pandemic Lockdown

Abstract: BackgroundEmotion and quality of life may have been impacted by the coronavirus disease 2019 (COVID-19) crisis, especially in the lockdown. The impact of temporomandibular disorders (TMD) symptoms and tooth loss on mental status and Oral Health-Related Quality of Life (OHRQoL) are not fully understood in a stressful situation.ObjectivesWe aimed to investigate whether TMD and tooth loss were the impaired risks of psychological states and OHRQoL in COVID-19 lockdown, and attempt to explore other potential risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(49 reference statements)
1
3
0
1
Order By: Relevance
“…As most patients experienced chronic TMDs, the higher frequencies of the aforementioned conditions might be the consequence of intensified TMD pain and/or dysfunction or heightened concerns over TMD problems during the pandemic. Findings were consistent with the elevated levels of psychological distress, oral parafunction, and TMD symptoms reported during the COVID-19 pandemic [ 18 , 19 , 23 ]. Psychological distress was posited to trigger a cascade of events culminating in increased sympathetic activity and release of adreno-corticoid hormones leading to muscle vasoconstriction and amplified stress responses [ 15 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As most patients experienced chronic TMDs, the higher frequencies of the aforementioned conditions might be the consequence of intensified TMD pain and/or dysfunction or heightened concerns over TMD problems during the pandemic. Findings were consistent with the elevated levels of psychological distress, oral parafunction, and TMD symptoms reported during the COVID-19 pandemic [ 18 , 19 , 23 ]. Psychological distress was posited to trigger a cascade of events culminating in increased sympathetic activity and release of adreno-corticoid hormones leading to muscle vasoconstriction and amplified stress responses [ 15 ].…”
Section: Discussionsupporting
confidence: 80%
“…Psychological distress was posited to trigger a cascade of events culminating in increased sympathetic activity and release of adreno-corticoid hormones leading to muscle vasoconstriction and amplified stress responses [ 15 ]. This coupled with increased awake and/or sleep bruxism during the pandemic could result in sustained masticatory muscle contractions and exacerbation of TMD-related myalgia and headache [ 15 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few cross-sectional studies conducted during and one year after the Covid-19 pandemic indicated greater frequencies of symptoms and higher levels of psychological distress among individuals with TMDs [ 24 27 ]. Furthermore, both sleep quality and OHRQoL were also found to be diminished and related to TMDs [ 28 , 29 ]. Nevertheless, the two available prospective studies involving TMD patients yielded varied findings with one demonstrating greater psychological distress and another specifying no worsening of pain intensity and OHRQoL during the Covid-19 pandemic [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os sintomas de DTM e a perda de dentes prejudicaram a qualidade de vida relacionada a saúde oral durante o confinamento (WENG et al, 2022).…”
Section: Ano Inicial Da Pandemia De Sars-cov-2unclassified